Looking Back and Looking Forward Through the Lens of the Nursing Professional Development: Scope and Standards of Practice, 3rd Edition. Issue 6 (November 2017) - Harper, Mary G.; Maloney, Patsy; Shinners, Jean
Abstract : This final column in the Nursing Professional Development (NPD) Scope and Standards department provides five exemplars of incorporation of the scope and standards into NPD practice and ends with a call to action for all NPD practitioners.